2019
DOI: 10.1021/acs.nanolett.9b02214
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Phonon Polariton Heat Transport

Abstract: As is well-known, the phonon and electron thermal conductivity of a thin film generally decreases as its thickness scales down to nanoscales due to size effects, which have dramatic engineering effects, such as overheating, low reliability, and reduced lifetime of processors and other electronic components. However, given that thinner films 1 have higher surface-to-volume ratios, the predominant surface effects in these nanomaterials enable the transport of thermal energy not only inside their volumes but also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 32 publications
1
49
0
Order By: Relevance
“…The SPHP contribution to the thermal conductivity of polar nanofilms was modeled and quantified by Chen et al [1], who reported a thermal conductivity of 4 Wm −1 K −1 for a 40-nm-thick SiO 2 film suspended in vacuum at 500 K. This prediction of the kinetic theory is more than twice the intrinsic phonon thermal conductivity of SiO 2 , was confirmed by means of the fluctuation-dissipation approach [4], and extended for films deposited over a substrate [2], other polar materials [19], layered systems [20][21][22], and arrangement of particles [23][24][25]. On the experimental side, on the other hand, Tranchant et al [26] measured the in-plane thermal conductivity of suspended SiO 2 nanofilms and showed up its clear increase as the film thickness reduces through values smaller than 50 nm. More recently, by measuring the temperature evolution of the in-plane thermal conductivity of SiN nanofilms, Wu et al [5] found that its values doubles up as the temperature raises from 300 to 800 K. This thermal conductivity enhancement for thinner and hotter polar nanofilms represents the fingerprints of the SPHP heat transport [1,2] and hence its experimental observation [5,26] provides decisive evidence for the potential application of SPHPs as long-distance heat dissipators.…”
Section: Introductionmentioning
confidence: 65%
“…The SPHP contribution to the thermal conductivity of polar nanofilms was modeled and quantified by Chen et al [1], who reported a thermal conductivity of 4 Wm −1 K −1 for a 40-nm-thick SiO 2 film suspended in vacuum at 500 K. This prediction of the kinetic theory is more than twice the intrinsic phonon thermal conductivity of SiO 2 , was confirmed by means of the fluctuation-dissipation approach [4], and extended for films deposited over a substrate [2], other polar materials [19], layered systems [20][21][22], and arrangement of particles [23][24][25]. On the experimental side, on the other hand, Tranchant et al [26] measured the in-plane thermal conductivity of suspended SiO 2 nanofilms and showed up its clear increase as the film thickness reduces through values smaller than 50 nm. More recently, by measuring the temperature evolution of the in-plane thermal conductivity of SiN nanofilms, Wu et al [5] found that its values doubles up as the temperature raises from 300 to 800 K. This thermal conductivity enhancement for thinner and hotter polar nanofilms represents the fingerprints of the SPHP heat transport [1,2] and hence its experimental observation [5,26] provides decisive evidence for the potential application of SPHPs as long-distance heat dissipators.…”
Section: Introductionmentioning
confidence: 65%
“…According to Equation ( 17), these lowest and highest values of the SPhP transmissivity drive the behavior of the thermal conductivity spectrum, which takes higher values for shorter nanowires, as shown in Figure 6a. At high enough frequencies, this spectrum becomes independent of the nanowire length and decays exponentially due to the insufficient thermal energy required to excite them, as established by the Bose-Einstein distribution function involved in Equation (17). At very low frequencies, on the other hand, the thermal conductance spectrum takes its highest values due to the high transmissivity of SPhPs.…”
Section: Resultsmentioning
confidence: 97%
“…The limitations of phonons and electrons to exhibit 1D ballistic heat conduction at temperatures comparable to room temperature, can be overcome with surface phononpolaritons (SPhPs), which are evanescent electromagnetic waves generated by the hybridization of photons and phonons at the interface of polar materials [10][11][12][13][14][15][16][17][18]. This ballistic behavior appears due to the huge SPhP propagation length that was found to be as long as 1 m [19][20][21][22] and is hence orders of magnitude longer than the typical mean free paths of electrons and phonons.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al have reported that the SPhP thermal conductivity of a 40 nm-thick thin film of amorphous SiO suspended in air is 4 Wm K at 500 K, which is higher than its bulk phonon thermal conductivity [ 11 ]. An experimental demonstration was also conducted by Tranchant et al [ 24 ]. They reported that the in-plane thermal conductivity of a SiO film increases by more than 50% of that of bulk SiO for a film thickness less than 50 nm.…”
Section: Introductionmentioning
confidence: 99%